“Philosophical Expression Through Language in Postmodern English Literature” (Texas Journal of Philology, Culture and History, 2026)
It argues that key postmodern features—skepticism toward metanarratives, intertextual play, metafictional architecture, semantic indeterminacy, and shifts across discourses—are primarily enacted at the level of language. The theoretical framework draws on accounts of linguistic self-reference, differential meaning, the redefinition of the author–text relation, and the reader’s role in meaning production. Using a typological analysis of selected postmodern English novels and narrative strategies, the study demonstrates that language in postmodern texts is not a transparent medium reflecting “reality” but a productive mechanism that stages philosophical problems: plurality of truth, fragmented identity, the constructed nature of time and memory, and the limits of knowledge